Prognostic impact of lymph node spreading pattern in N2 NSCLC patients. Issue 3 (4th March 2023) - Schlachtenberger, Georg; Doerr, Fabian; Menghesha, Hruy; Amorin, Andres; Hoepker, Katja; Hagmeyer, Lars; Wahlers, Thorsten; Hekmat, Khosro; Heldwein, Matthias B.
ABSTRACT: Background: One-third of non-small cell lung cancer (NSCLC) patients are diagnosed with locally advanced disease. Long-term survival in stage IIIA/B-N2 remains poor; this may also be due to lymph node spreading pattern. Therefore, we compared the overall survival of stage IIIA/B-N2 patients with superior mediastinal lymph nodes (SML) with infracarinal- or inferior mediastinal lymph nodes (IML) and with multilevel disease (MLD). Research design and methods: One-, three-and five-year survival rates were measured. Kaplan-Meier curves and Cox proportional hazards model assessed survival and were used to identify prognostic factors. Results: We reviewed data of stage IIIA/B-N2 patients (n = 129) who underwent surgery for NSCLC between 2012 and 2020. Patients with SML (n = 62) were compared to ILM (n = 37) and MLD (n = 30). SML patients showed significantly better one- (SML: 95.2% vs. IML: 78.6% vs. MLD: 69.4%, p = 0.03), three- (78.8% vs. 27.7 vs. 13.3%; p = <0.001) and five-year (61.1% vs. 17.1 vs. 3%; p < 0.001) survival rates, than IML and MLD patients. Kaplan-Meier curves showed prolonged overall survival for SML patients (log-rank SML, ILM, MLD p < 0.0001). Conclusions: This study showed significantly better long-term survival of SML patients than IML and MLD patients. The long-term survival of ILM and MLD patients was equally poor.